Correction: APTES assisted surface heparinization of polylactide porous membranes for improved hemocompatibility. Issue 25 (17th April 2018) - Li, Jinglong; Liu, Fu; Yu, Xuemin; Wu, Ziyang; Wang, Yunze; Xiong, Zhu; He, Jidong
Abstract : Correction for 'APTES assisted surface heparinization of polylactide porous membranes for improved hemocompatibility' by Jinglong Li et al., RSC Adv., 2016, 6, 42684–42692.